As time goes by - Overlooking 40 years of inpatient burn treatment at a national pediatric burn center in Switzerland - Elrod, Julia; Adathal, Ashal; Mohr, Christoph; Neuhaus, Kathrin; Schiestl, Clemens; Böttcher-Haberzeth, Sophie (Burns, 2023)
BACKGROUND: Despite extensive prevention programs, burns remain a frequent cause of injury in Switzerland with a known age peak in children. Pediatric burns may cause substantial morbidity, a psyochological burden and therapy related high economic costs. To improve preventive measures, precise knowledge of etiology and treatment of pediatric burns in Switzerland as well as their temporal evolution is indispensable. - METHODS: The present retrospective analysis included pediatric burn patients admitted for acute treatment to the Pediatric Burn Center of the University Children`s Hospital Zurich over the last four decades. Sociodemographic, injury related, and treatment related data were extracted from medical records. Linear regression analysis was applied to determine temporal changes during the past four decades and chi-square and t-tests were applied wherever applicable. - RESULTS: A total of 3425 acute burn patients were included in the study between 1977 and 2020, corresponding to a mean of 89 patients/year. Mean age was 3.60 ± 4.12 years, three quarters of all patients were preschool children (0-5 years) and mean total body surface area (TBSA) burned was 8.01% ± 9.57%, however only around one fifth had severe burns (>10% TBSA). Scald burns (65.31%) and flame burns (32.99%) were most commonly seen. Linear regression analysis showed the total number of thermal injuries treated at our center to have increased significantly as of 2004 (p < 0.001). Separate analysis showed the same for small and medium (<10% TBSA) burns (p < 0.001), whereas the number of severe burns did not increase significantly. Length of stay (LOS) was highly associated with %TBSA burned. The percentage of female patients amongst all patients increased over time (p = 0.012). LOS per TBSA burned decreased significantly (p < 0.001). - CONCLUSION: The present data show pediatric burns to remain a major health burden in Switzerland, especially small and medium burns in preschool children. Prevention programs should focus on this age population as well as on scald and flame burns as most common etiologies. The observed decrease in length of stay suggests a major improvement in overall quality of care in pediatric burns and supports centralization of care.
Gesehen am 19.07.2024